Analisis Kompetensi Profesional Guru Fikih Lulusan Prodi PAI FITK UIN Sumatera Utara di MTsN Kota Medan - As'Ad; Enny Nazrah Pulungan (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2025)
This study aims to analyze the professional competence of Islamic jurisprudence teachers alumni of the Islamic Religious Education Study Program (PAI) UIN North Sumatra at MTsN Medan City. The method used in this study is descriptive, qualitative with a phenomenological approach. Data collection techniques, through observation, interviews, and documentation. Data analysis techniques with triangulation and member crosscheck. The results of this study indicate that UIN SU alumni fiqh teachers at MTsN Medan City have high professional competence, marked by teacher certification, mastery of knowledge, and commitment to the profession. They actively develop skills through continuing education and training to adapt to technological developments and learner needs. The use of innovative educational technology is also their hallmark in creating effective and interactive learning. The main supporting factor for the development of professional competence of fiqh teachers is the support of the madrasah principal in granting training permits. In addition, they actively participate in the Subject Teachers' Conference (MGMP) to share experiences, teaching strategies, and the latest curriculum developments.